Հայաստանի Հանրապետության ինքնիշխանության հիմնախնդիրը սահմանադրական ժամանակակից գործընթացում - Արամ Խաչատրյան (ՀՀ ԳԱԱ հրատ.)
В статье затронуты проблемы исследования суверенитета конституционного закрепления и урегулирования в контексте конституционных реформ Республики Армения. Обобщая результаты системного анализа закрепленных в Конституции Республики Армения, определены современные тенденции и проблемы суверенитета конституционного регулирования, представлены соответствующие предложения в рамках конституционных реформ. The article touches upon the study problem of the sovereignty of constitutional securing and settlement in the context of constitutional reforms, in the Republic of Armenia. Summarizing the results of the system analysis set forth in the Constitution of the Republic of Armenia, the author identified current trends and problems of constitutional regulation sovereignty, provided relevant proposals within the framework of constitutional reforms.
Keywords: Law